Selection of some Hybrids of Poncirus trifoliata (L.) Raf. Tolerant to Freezing Stress by using some Growth Markers and Chemical and Enzymatic Indicators - خوجه, حسان; الخطيب, علي; حسن, فينوس (Latakia University Journal -Biological Sciences Series, 2021)
The study was conducted during 2019-2020 at the Agricultural Scientific Research Center in Lattakia. Poncirus trifoliata were used as (Pollen Parent), Cleopatra, and Sour orange as (Seed Parent). The seeds of F1 were sown in agricultural pots, and the resulting plantings were transferred in February to a refrigerator, where they were exposed to cold gradually reaching (-2)°C m and then to (-10)°C. As a result, cold stress (-2)°C resulted in the death of 50% of the tested seedlings, and when the temperatures were reduced to (-10)°C, led to damage to the remaining seedlings, and the percentage of damage reached up to (30%) of the implant, but this seedling regained its life in the next growing season and continued its activity, Some growth indicators were calculated, the average length and diameter of the implant, and the hybrids produced by the female Cleopatra gave the best results, especially the hybrids (210, 201, 233 and 220). the height reached 100 cm in the hybrid (210), as for the damage percentage, it ranged between 7% when the hybrid 322 female sour orange to 30% at (210, 204, 200, 203 and 202) female Cleopatra, as for the activity of the peroxidase enzyme, where the enzyme activity increased at (-10)°C compared to its activity at (-2)°C and in high statistical significance, and the highest values ​​were when the hybrid 202 femal Cleopatra, and when the hybrid (322) the femal sour orang, and when calculating the specified difference for the enzyme activity, the hybrids (350, 300, 322 and 320) outperformed the hybrids (233, 231, 240, 243, 203 and 223) with a high statistical significance. Regarding the total chlorophyll index, the highest values ​​were at (322) femal Sour orang and the hybrid (202) femal Cleopatra, with significant differences in high statistical significance between the amount of chlorophyll at (-2)°C and its quantity at (-10)°C, and it was found when calculating the specified difference among the studied hybrids in terms of total chlorophyll values ​​was the superiority of the hybrids 322, 320 and 202 over the rest of the hybrids.